Reconfiguration of standards data for improved production planning. (1st January 2002) - Moynihan, Gary P.; Gurley, Dana S.; Ray, Paul S.; Albright, Thomas L.
In most ERP and MRP systems, the bill of material and the time standards file represent the fundamental data sources used for subsequent processing. This paper addresses the improved systemic use of time standards for such processing functionality. Standards represent time estimates for normal task durations. In a manufacturing environment, the standards file provides data to drive such ERP and MRP functions as production planning and scheduling, estimating, and performance measurement. However, the resulting production plan may be in error due to the inclusion of incomplete operational aspects. Although some classical industrial engineering techniques provide insight into these aspects, the standards data are not stored in a structure adequate for detailed production planning. A reconfiguration in the structure of standards data is proposed in this paper. This restructuring has significant implications for the improved accuracy of production plans, and the enhanced affordability of the resulting product.